The Development of Community Enterprise Entrepreneurs in the Crop Production Sector for Entry into e-Commerce - Krisada Chienwattanasook; Krit Jarinto; Madaoh Sulong (My University, 2023)
The spread of coronavirus disease in 2019 (COVID -19) in Thailand has led to a lack of liquidity and income for entrepreneurs, increasing the variety of distribution channels compared to store sales. This will be a solution for businesses that are struggling. The objectives of this research are to provide training and guidance to community enterprise groups, build a platform and collect product data from community enterprises in the research area, i.e. community enterprises in Chachoengsao Province. This research is participatory action-based with a group of entrepreneurs and 25 groups of community enterprises with three main processes: first, selection and training on e-commerce, second, development of electronic databases and marketing consultation to collect data from the website and consult experts. Finally, advertising and publicity in the online media to make consumers and the general public aware of the project in order to increase the sales and revenues of the community enterprise entrepreneurs. The results of the study indicate political and practical recommendations. To begin with, the government should provide financial support such as low-interest funds or loans as well as have clear, concrete, and continuity policies to support and promote community enterprises. In addition,community enterprises should raise awareness about the importance of real participation, manage big data, and form online trading will facilitate which can ensure sustainability.
Keywords: Innovation and Socioeconomic Development